2014
DOI: 10.1097/psn.0000000000000032
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Formal Complaints in 1,645 Liposuction Operations

Abstract: a total of 1,645 patients underwent primary liposuction by the fi rst author. Secondary liposuction and liposuction, combined with other procedures, were excluded. There were 1,330 women and 315 men in the group studied whose average age was 34 years. MethodsAn analysis of all completed complaint investigations within this patient cohort was undertaken.Complaints were categorized into the following:1. Aesthetic concerns. 2. Complications of surgery.3. Quality-of-care issues such as delayed time to operation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The invalidity or inadequacy of informed consent was a recurring subject of dispute, and was frequently included among the motivations of convictions (in 34% of judgments and 48.5% of convictions), especially for cosmetic procedures, confirming the importance of acquiring an adequate consent to the treatment and the need of effective preoperative communication with the patient in order to prevent litigation, as highlighted in other studies [17][18][19][20][21][22]. Particularly, Bismark et al reported that, in 70% of cases, the complaints concerned insufficient information about the adverse effects and complications of procedures, in 39% of cases, the lack of information about the possibility of no benefit from treatment, and in 26% the inappropriate process of acquiring consent [21].…”
Section: Discussionmentioning
confidence: 94%
“…The invalidity or inadequacy of informed consent was a recurring subject of dispute, and was frequently included among the motivations of convictions (in 34% of judgments and 48.5% of convictions), especially for cosmetic procedures, confirming the importance of acquiring an adequate consent to the treatment and the need of effective preoperative communication with the patient in order to prevent litigation, as highlighted in other studies [17][18][19][20][21][22]. Particularly, Bismark et al reported that, in 70% of cases, the complaints concerned insufficient information about the adverse effects and complications of procedures, in 39% of cases, the lack of information about the possibility of no benefit from treatment, and in 26% the inappropriate process of acquiring consent [21].…”
Section: Discussionmentioning
confidence: 94%